Analysis of Underwater Topographic Survey of Stilling Basin Based on Unmanned Survey System. (2nd April 2021) - Xie, Hui; Wang, Haoran; Yang, Yayi; Chen, Yongcan; Yang, Jun; Wang, Shuang; Liu, Zhaowei
Abstract : The combination of Global Positioning System-Real Time Kinematic (GPS-RTK) and depth sounder is an important technical method of modern underwater topographic survey. In this paper, the combined technology was integrated with unmanned surface vehicle (USV) technology to construct an unmanned survey system suitable for underwater topographic survey in stilling basin, and it was applied to survey the underwater topography of the stilling basin of Tingzikou hydrojunction project. Based on the surveying and mapping data and 3D model, the trend of elevation change of the stilling basin including apron, end sill, antiscour section, and river convergence section was analyzed. The results show that, for the surface outlet stilling basin of Tingzikou, after flood, the structure is complete, the boundaries are clear, the water quality is good, and there is little sediment on the surface of apron from overflow dam section to end sill. Furthermore, no obvious sediment or structural abnormality has been found in the still basin. Affected by the bedrock and cofferdam cobble gravel sediment, the elevation of the antiscour section and the downstream convergence section of the surface outlet stilling basin increased significantly. For the bottom outlet stilling basin of Tingzikou, there is large sediment within a range of 20 m∼40 m from the bottom sill and the maximum height of it reaches 2.04 m, while there is no obvious sediment or structural abnormality in the remaining region of basin. The critical sedimentation height can effectively judge the safety grade of the sedimentation height in stilling basin and provide a reliable support for assessing the overall safety of stilling basin. The application of unmanned survey technology improves the accuracy and timeliness of underwater topography and sedimentation distribution of stilling basin, which has significant application research value and promotion significance.